Bicyclo[3.2.1]amide-DNA: A chiral, nonchiroselective base-pairing system - Ahn, DR; Egger, A; Lehmann, C; Pitsch, S; Leumann, CJ (WILEY-V C H VERLAG GMBH, 2002)
The design, synthesis, and base-pairing properties of bicyclo[3.2.1]amide-DNA (bca-DNA), a novel phosphodiester-based DNA analogue, are reported. This analogue consists of a conformationally constrained backbone entity, which emulates a B-DNA geometry, to which the nucleobases were attached through an extended, acyclic amide linker. Homobasic adenine-containing bca decamers form duplexes with complementary oligonucleotides containing bca, DNA, RNA, and, surprisingly, also L-RNA backbones. UV and CD spectroscopic investigations revealed the duplexes with D- or L-complements to be of similar stability and enantiomorphic in structure. Bca oligonucleotides that contain all four bases form strictly antiparallel, left-handed complementary duplexes with themselves and with complementary DNA, but not with RNA. Base-mismatch discrimination is comparable to that of DNA, while the overall thermal stabilities of bca-oligonucleotide duplexes are inferior to those of DNA or RNA. A detailed molecular modeling study of left- and right-handed bca-DNA-containing duplexes showed only minor changes in the backbone structure and revealed a structural switch around the base-linker unit to be responsible for the generation of enantiomorphic duplex structures. The obtained data are discussed with respect to the structural and energetic role of the ribofuranose entities in DNA and RNA association.
Keywords: HEXOSE-NUCLEIC ACIDS; HYBRIDIZATION PROPERTIES; DUPLEX STABILITY; RIGID BACKBONE; DNA ANALOG; RNA; OLIGONUCLEOTIDES; RECOGNITION; ADENINE; THYMINE